STRATEGI PERUSAHAAN MENUJU ORGANISASI LINCAH - Nazmah Nazmah; Achmad Yani (Jurnal Kompetitif, 2023)
This research uses a qualitative method with data collection using in depth interview techniques for structural officials in the XCG organization and also FGD (Focus Group Discussion) for structural officials. the technique used is the Delphi Techniques and Purposive sampling techniques. The sample in this study was 125 people with the level of branch heads. The purpose of this study was to determine the organization's strategy in digital system changes towards an agile organization. In this study obtained a conclusion, (1) Changes in the economic and political situation are also external factors that get special attention in developing strategies in the organization, (2) readiness of resources (manpower), (3) openness in decision making, and (3) reward system. Abstrak Penelitian ini menggunakan metode kualitatif dengan pengambilan data menggunakan teknik in depth interview terhadap pejabat struktural di organisasi XCG dan juga FGD (Focus Group Discussion) terhadap pejabat struktural.teknik yang digunakan adalah Teknik Delphi (Delphie Techniques) dan teknik pengambilan sampel Purposive sampling. Sampel dalam penelitian ini sebanyak 125 orang dengan tingkatan kepala cabang. Tujuan dari penelitian ini untuk mengetahui strategi organisasi dalam perubahan sistem secara digital menuju organisasi yang lincah. Pada penelitian ini diperoleh suatu kesimpulan, (1) Perubahan situasi ekonomi dan politik juga merupakan faktor external yang mendapatkan perhatian khusus dalam Menyusun strategi didalam organisasi, (2) Kesiapan sumberdaya (manpower), (3) keterbukaan dalam pengambilan keputusan, serta (3) system reward.